Linking Social Cognition, Parvalbumin Interneurons, and Oxytocin in Alzheimer's Disease: An Update - Černotová, Daniela; Hrůzová, Karolína; Levčík, David; Svoboda, Jan; Stuchlík, Aleš (Journal of Alzheimer's disease, 2023)
Finding a cure for Alzheimer's disease (AD) has been notoriously challenging for many decades. Therefore, the current focus is mainly on prevention, timely intervention, and slowing the progression in the earliest stages. A better understanding of underlying mechanisms at the beginning of the disease could aid in early diagnosis and intervention, including alleviating symptoms or slowing down the disease progression. Changes in social cognition and progressive parvalbumin (PV) interneuron dysfunction are among the earliest observable effects of AD. Various AD rodent models mimic these early alterations, but only a narrow field of study has considered their mutual relationship. In this review, we discuss current knowledge about PV interneuron dysfunction in AD and emphasize their importance in social cognition and memory. Next, we propose oxytocin (OT) as a potent modulator of PV interneurons and as a promising treatment for managing some of the early symptoms. We further discuss the supporting evidence on its beneficial effects on AD-related pathology. Clinical trials have employed the use of OT in various neuropsychiatric diseases with promising results, but little is known about its prospective impacts on AD. On the other hand, the modulatory effects of OT in specific structures and local circuits need to be clarified in future studies. This review highlights the connection between PV interneurons and social cognition impairment in the early stages of AD and considers OT as a promising therapeutic agent for addressing these early deficits.
Keywords: kognice; Mice, Transgenic; lidé; myši transgenní; Cognition; parvalbuminy; prospektivní studie; Parvalbumins; interneurony; Alzheimerova nemoc; Hippocampus; Humans; oxytocin; Prospective Studies; Disease Models, Animal; Oxytocin; Alzheimer Disease; Interneurons; zvířata; Animals; sociální kognice; Social Cognition; hipokampus; modely nemocí na zvířatech